Recent Advances in Forest Microclimate Research in India - Subba Rao, B. K.; Rawat, Laxmi (Indian Forester, 1987)
The paper reviews the recent research advances in forest microclimatology in India. Most of tbe studies have been carried out in forest plantations at F.R.I., Dehra Dun and natural sal forests nearby. Salient results of the studies have been brought out.